Students’ Feedback and Communication Habits using Moodle - Hölbl, M.; Welzer, T. (Elektronika ir Elektrotechnika, 2010)
eLearning has managed to penetrate into most classrooms nowadays and Moodle is one of wider accepted LMS. After years of its application in everyday teaching practice we were inspired to analyse the student communication and feedback habits using Moodle. In this paper, we will present the experiences and results of a questionnaire regarding Moodle and eLearning. Firstly we analyse which communications capabilities of Moodle. Additionally, we present an analysis of students’ feedback habits using Moodle regarding the grading of teachers, teaching assistants and the course in general. Finally, we also investigate student’s general opinion on eLearning and experiences with technical problem when using Moodle.